2021
DOI: 10.1002/essoar.10505084.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Improved Perturbation Pressure Closure for Eddy-Diffusivity Mass-Flux Schemes

Abstract: An analytical closure for the perturbation pressure in turbulence and convection parameterizations is derived.• The closure combines the effects of virtual mass, momentum convergence, and pressure drag.• The closure performs well in simulating a rising bubble and the diurnal cycle of deep convection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We consider the EDMF scheme discussed in Cohen et al (2020); Lopez-Gomez et al (2020), which is implemented in a single-column model (SCM). Within this SCM, we first seek to learn 16 closure parameters: Five describing turbulent mixing, dissipation, and mixing inhibition by stratification (Lopez-Gomez et al, 2020), three describing the momentum exchange between subdomains (He et al, 2021), seven describing entrainment fluxes between updrafts and the environment (Cohen et al, 2020), and another one defining the surface area fraction occupied by updrafts. In Section 4.4, we substitute the empirical dynamical entrainment closure proposed in Cohen et al (2020) by a neural network, and train the resulting physics-based machine-learning model.…”
Section: Application To An Atmospheric Subgrid-scale Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider the EDMF scheme discussed in Cohen et al (2020); Lopez-Gomez et al (2020), which is implemented in a single-column model (SCM). Within this SCM, we first seek to learn 16 closure parameters: Five describing turbulent mixing, dissipation, and mixing inhibition by stratification (Lopez-Gomez et al, 2020), three describing the momentum exchange between subdomains (He et al, 2021), seven describing entrainment fluxes between updrafts and the environment (Cohen et al, 2020), and another one defining the surface area fraction occupied by updrafts. In Section 4.4, we substitute the empirical dynamical entrainment closure proposed in Cohen et al (2020) by a neural network, and train the resulting physics-based machine-learning model.…”
Section: Application To An Atmospheric Subgrid-scale Modelmentioning
confidence: 99%
“… Note. The prior mean values are taken from LG2020 (Lopez‐Gomez et al., 2020), C2020 (Cohen et al., 2020), and H2021 (He et al., 2021), where a physical description of the parameters may be found. …”
Section: Application To An Atmospheric Subgrid‐scale Modelmentioning
confidence: 99%
“…This runtime was chosen to be much longer than the equilibration time of the SCM to the steady forcing; experiments using a runtime of 12 Table 1: Parameters φ considered for calibration in this study. The prior mean values are taken from LG2020 (Lopez-Gomez et al, 2020), C2020 (Cohen et al, 2020) and H2021 (He et al, 2021), where a physical description of the parameters may be found.…”
Section: Description Of Les Data and Model Configurationsmentioning
confidence: 99%
“…The extended eddy diffusivity mass flux (extended‐EDMF) scheme (a close cousin of the multifluid model that extends traditional EDMF schemes to include transience; Tan et al, 2018) has seen substantial progress in recent years, with the formulation of new closures and successful single‐column simulations of various moist convective regimes, including shallow convection (Cohen et al, 2020; He et al, 2020; Lopez‐Gomez et al, 2020). Rapid progress has also been made in developing the multifluid approach, including new numerical methods (Weller and McIntyre, 2019), new closures (Weller et al, 2020), and accurate simulations of dry convection (Thuburn et al, 2019; Weller et al, 2020; Shipley et al, 2022).…”
Section: Introductionmentioning
confidence: 99%